Perception of Community Medicine as a subject and career preference among undergraduates - Saleha Afreen; Susmitha KM; P. Bhuvaneswari; P. Sasikala; Pravallika S; S. Govindu (Global Journal of Medicine and Public Health)
Background Community Medicine (CM) teaches undergraduates about the needs of both healthy and unhealthy individuals as well as how to plan and administer healthcare services. Undergraduate students benefit greatly from a curriculum that integrates comprehensive health care with community engagement, prevention, and health promotion. Objective The objective of this study is to assess the perception of undergraduate medical students and interns regarding community medicine as a subject and as a career option. Methodology An observational cross-sectional study was conducted between April and November 2024 among undergraduate medical students and interns at ACSR Government Medical College, Nellore, using purposive sampling method. Predesigned, pretested self-administered structured questionnaire (Google form) was used as a data collection tool for data collection. Results Out of 700 students who participated in the study, 357 (51%) were females and 343 (49%) were males. The majority, 87 (69.6%), were from urban areas. 598 (85.4%), students understood the concept of community medicine, 612 (87.4%) of them feel that community medicine has improved their problem-solving skill. 687 (98.1%) students feel that the knowledge and experiences will be useful for their career as a doctor and 483 (69%) feel that preventive medicine is better than curative medicine. Only 128 (18.3%) students consider pursuing community medicine as a career option due to low income and few opportunities of treating patients. Conclusion Students understood the concept and relevance of community medicine; however, they did not choose it as a future career option.